Screening and identification of aquatic bacteriocinogenic Bacillus strains inhibiting clinical MRSA and VRE from Pakistan - RIZVI, RUBAB ZEHRA; WAHAB, ABDUL; Pirzada, Zaid Ahmed (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: The purpose of current study is to screen and identify novel bacteriocinogenic strains from marine, fresh and estuarine water bodies which can serve as alternatives to the antibiotics, as the antibiotic resistance is on the rise. Methodology: Altogether seven fresh, brackish and marine water samples from various regions of Sindh were collected All the aquatic bacterial strains were isolated by standard plate count and overlay methods. The bacteriocinogenic strains were screened by spot agar, stab and overlay, cross streak and agar well-diffusion techniques. Results: Out of the total 146 isolates, 41 (28%) were bacteriocinogenic, among which 28 (68%) were isolated from freshwater, 12 (29%) from marine and 1 (3%) from brackish water. The most significant bacteriocinogenic strains amongst the isolates were identified as B coagulans, B simplex, B macerans and B circulans. When tested against 17 significant pathogens, these strains could inhibit various clinical drug resistant Gram positive pathogens like Staphylococcus aureus and Methicillin resistant Staphylococcus aureus (MRSA), Streptococcus pyogenes, S agalactiae and Vancomycin resistant Enterococcus (VRE) and C diptheriae. Furthermore, Escherichia coli and Klebsiella spp. were observed to be sensitive against two bacteriocinogenic strains of B coagulans. Furthermore, 59% of the aquatic isolates were sensitive against one of theÂ  bacteriocinogenic strain indicating competitive antagonism phenomenon. Conclusion: This research study reveals the bacteriocinogenic potential of indigenous aquatic isolates against drug resistant clinical pathogens as well as against fish pathogens.